A Secure Mobile Wireless Sensor Networks based Protocol for Smart Data Gathering with Cloud. (January 2022) - Haseeb, Khalid; Jan, Zahoor; Alzahrani, Fahad A; Jeon, Gwanggil
ABSTRACT: The lightweight sensors gain rapid growth for the development of emerging technologies due to multi aspects. Recently, many applications are integrating with the cloud services for storage and processing a large amount of observing data, however, the transitory and time-dependent environment needs valuable performance. Also, reliable and error-free data transmission is an important factor for green systems. Moreover, most of the proposed green networks may be exposed to unspecified events due to the broadcast nature of the unreserved medium. This research paper presents a secured mobile sensor network based protocol for smart data gathering with cloud services (S-SDC), which aims to attain information distribution in dynamic networks using mobile sensors with minimum loss and power consumption. Also, it ensures network availability and consistency for the collected data with the cloud corporations and increases authoritative routing. The simulation results and their analysis are proven the significant performance of the proposed protocol. Graphical Abstract: Image, graphical abstract